Ovarian cycle in Devario aequipinnatus with emphasis on oogenesis - De Jesus-Silva, Laíza Maria [UNESP]; De Oliveira, Pricila Viana [UNESP]; Da Silva Ribeiro, Cristiéle [UNESP]; Ninhaus-Silveira, Alexandre [UNESP]; Veríssimo-Silveira, Rosicleire [UNESP] (Cambridge University Press (CUP), 2018)
Summary This study aimed to understand how germ cell development occurs in females of Devario aequipinnatus, by morphologically describing oogenesis and the reproductive phases. Sexually mature females of D. aequipinnatus (n = 70) were obtained from commercial fisheries and delivered to the Laboratório de Ictiologia Neotropical, UNESP, Ilha Solteira, SP, Brazil. The ovaries were removed, fragmented and fixed following the usual techniques for light microscopy. The stages of ovarian development in D. aequipinnatus begin with the oogonia, which proliferate into new cells or differentiate into prophasic oocytes that, at the end of this process, form the ovarian follicle and end folliculogenesis. In the previtellogenic stage, the oocytes were characterized mainly by the gradual loss of basophilia and an increase in oocyte diameter. Vitellogenesis was marked mainly by the incorporation of yolk granules. Mature oocytes were defined by their migration from the nucleus to the micropyle. Postovulatory follicles and atresic oocytes were also observed. The reproductive phases were classified as: immature, early and final developing, spawning capable, regressing and regenerating. Therefore, the development of an understanding of cell modifications that occurs up to oogenesis is a basic step that is essential for the description of the reproductive biology of D. aequipinnatus, given the lack of information about the reproductive aspects of this species.
Keywords: Danio; Fish; Germ cells; Morphology; Reproduction